Electromagnetism metaheuristic algorithm for solving the strong minimum energy topology problem - Kartelj, A. (Yugoslav Journal of Operations Research; Vol 23 No 1 (2013): Vol. 23 No. 1, 2016)
In this paper electromagnetism (EM) metaheuristic is used for solving the NPhard strong minimum energy topology problem (SMETP). Objective function is adapted to the problem so that it effectively prevents infeasible solutions. Proposed EM algorithm uses efficient local search to speed up overall running time. This approach is tested on two sets of randomly generated symmetric and asymmetric instances. EM reaches all known optimal solutions for these instances. The solutions are obtained in a reasonable running time even for the problem instances of higher dimensions.